Presence in the television network in Spain parliamentary - Ana Terroso Conejero; Jorge Caldera-Serrano (Cuadernos de Documentación Multimedia, 2014)
Web expressions televisions assemblies and regional parliaments (besides the courts and the senate) of Spain, in order to verify at first its existence and form of distribution, either by own present analyzes the Net or by other mechanisms or third channels as using Youtube as channels broadcasting platform. Not only analyzes the presence or existence of such channels, but the broadcast format and the existence of elements of a conservation system and document storage as the existence of video libraries, and historical queries possibilities of audiovisual documents. As a state of the existence of different experiences of parliamentary televisions worldwide are listed as well as a quick run through the evolution of television types offered.